2020
DOI: 10.3382/ps/pez500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hevea brasiliensis seed meal or Euphorbia heterophylla seed supplemented diets on performance, physicochemical and sensory properties of eggs, and egg yolk fatty acid profile in guinea fowl (Numida meleagris)

Abstract: A total of 144 French selected breed (Galor) female guinea fowl (GF) of 42 wk of age were enrolled for a feeding trial of 15, 30, and 45 D duration. The birds were randomly assigned to 18 cages, each containing 8 birds. A total of 3 isonitrogenous and isocaloric dietary treatments were trialed, each diet comprising 6 replications (cages), which meant a total of 48 birds per diet. The GF were fed either a control diet C (commercial diet “FACI ponte 20”, SIPRA, Ivory Coast, usually used for all poultry species) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
2
7
3
Order By: Relevance
“…Hepatic serum levels of ALT and AST are frequently used to evaluate liver injuries. In this study, there were no significant changes in serum ALT and AST levels in the U. cannabina group compared with the control group, which confirms that there was no diet-induced liver injury [37]. A decrease in total cholesterol and triglycerides and an increase in HDL-cholesterol was observed in the serum of hens fed with U. cannabina due to the rich sterols content of U. cannabina.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Hepatic serum levels of ALT and AST are frequently used to evaluate liver injuries. In this study, there were no significant changes in serum ALT and AST levels in the U. cannabina group compared with the control group, which confirms that there was no diet-induced liver injury [37]. A decrease in total cholesterol and triglycerides and an increase in HDL-cholesterol was observed in the serum of hens fed with U. cannabina due to the rich sterols content of U. cannabina.…”
Section: Discussionsupporting
confidence: 64%
“…ALA is the pre-dominant fatty acid, accounting for 40.7% of the fatty acids in the mature leaves [5]. The composition of fatty acids stored in monogastric animals largely indicates that the lipid and fatty acid composition of poultry eggs can be altered by diet [37]. Hence, eggs can be an important source of n-3 PUFA when laying hens are fed a diet containing a high level of n-3 PUFA [11,38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was showed that the fat metabolism of pigs was modulated by 500 mg/kg nettle extract in diet, that the MUFA was decreased and PUFA was increased in muscle fat ( Szewczyk et al, 2006 ). The composition of fatty acids stored in monogastric animals indicated the possibility that the lipid and fatty acid composition of poultry eggs could be altered by the diet ( Kouassi et al, 2020 ). In the present study, 6% ramie significantly increased the content of icosaic acid and ALA in egg yolk, and significantly increased the content of n-3PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…However, rapidly expanding demands for poultry products are not really stimulating the local poultry production as much as might be expected because of high levels of poultry product imports [2]. The egg-consumption rate is 64 eggs per Ivorian per year [3] and projections indicate a consumption of between 100 and 150 eggs per Ivorian per year by 2030 [4]. Indigenous poultry production in Africa has been neglected for a long time, because of its low productivity, even if the taste of the meat and eggs from these animals are highly appreciated by the population.…”
Section: Introductionmentioning
confidence: 99%